1997
DOI: 10.1063/1.872536
|View full text |Cite
|
Sign up to set email alerts
|

The influence of collisions on the plasma sheath transition

Abstract: In the asymptotic limit λD/λ→0 (where λD is the electron Debye length and λ represents the ion mean free path) the boundary layer of a collision dominated plasma is split up in a collision free planar sheath (scale λD) and a quasi-neutral presheath (scale λ). The “sheath edge” separating the presheath and the sheath is defined by the Bohm criterion. To clear up controversial statements on the validity of the plasma sheath concept and on the role of the Bohm criterion for finite values of λD/λ, a simple fluid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
195
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(205 citation statements)
references
References 24 publications
9
195
1
Order By: Relevance
“…The possibility of the existence of sheaths with subsonic ions at the edge was widely addressed in the literature, by exploring if the presheath processes (collisions, ionization) or the geometry could influence the transition to the non-neutral region [14,15]. It was concluded that the Bohm criterion, V i = c s , is a ubiquitous property of ion sheaths in the limit T i T e and λ D L [2,16]. In this article we rigorously derive the location of the sheath edge where quasineutrality is broken by using an appropriate kinetic description of the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of the existence of sheaths with subsonic ions at the edge was widely addressed in the literature, by exploring if the presheath processes (collisions, ionization) or the geometry could influence the transition to the non-neutral region [14,15]. It was concluded that the Bohm criterion, V i = c s , is a ubiquitous property of ion sheaths in the limit T i T e and λ D L [2,16]. In this article we rigorously derive the location of the sheath edge where quasineutrality is broken by using an appropriate kinetic description of the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The edge of the visible emission region corresponds to the edge of the quasineutral pre-sheath region from which ions exit with the Bohm speed, (kT e / M) 1/2 (T e : electron temperature, M: ion mass) acquired in the last mean free path [13]. At this point, the field increases monotonically up to the transition region field.…”
Section: Estimation Of Ion Bombardment Energymentioning
confidence: 99%
“…When a hypersonic vehicle reenters the atmosphere, severe friction between the aircraft and the ambient air results in a dramatic increase in the local temperature and pressure, which leads to intensified air ionization, and a layer of plasma flow is generated around the reentry vehicle [1]. The plasma flow, which consists of numerous free electrons, ions, and neutral particles, is nonmagnetic, lowtemperature, weakly ionized, and quasi-neutral (i.e., electricity neutral on macroscopic-length scales) [2,3].…”
Section: Introductionmentioning
confidence: 99%